Contribution to the knowledge of the macromycetes of the State of Michoacán - Díaz-Barriga, Horalia; Guevara-Féfer, Fernando; Valenzuela, Ricardo (Instituto de Ecología, A.C., 1988)
A list of 270 species of higher fungi from 72 localities from the State of Michoacán is presented. The list embraces 138 new records for the state. Some data about their distribution according to plant communities and substrata in habited are included.